PENGARUH BAURAN PEMASARAN JASA, KUALITAS LAYANAN DAN NILAI RELIGIUSITAS TERHADAP KEPERCAYAAN NASABAH DAN IMLIKASINYA PADA KOMITMEN NASABAH BANK UMUM SYARIAH DI WILAYAH GERBANG KERTASUSILA JAWA TIMUR. - Halik, Abdul (JHP17 (Jurnal Hasil Penelitian), 2016)
Countries which joined in the OKI founded the financial institutions thatprovide financial services based on fees and profit sharing to the OKI membercountries. The sharia banking in Indonesia is started in 1991 by a MuamalatIndonesia bank. The development of the market share until 2012 has reachedabout 4,62 %, it means that sharia banking must try hard to develop its marketshare. But the market share of sharia banking always loses with theconventional banks, it can only grow 1 percent per year, but the conventionalbanks can grow till 7 percent per year. According to Tjiptono (2007: 111) themarketing mix is the product, the price, distribution and promotion of thelocation and known as 4p, in addition the company can do differentiatecompetitive in the delivery of services through three aspects known 3p in themarketing services. The population on this study is the customers that they havethe bank account in the Sharia bank public and live in Gerbang Kertasusila area.From that population, this study uses sample of 200 respondents. A method ofsampling purposive is a technique of the determination of the sample based onchance, it means that anyone who by chance or incidental meet, when theymake a deal in the any Sharia bank or other place (home, office and etc.), withthe researcher can be used as the sample, if that person is considered suitable asa source of data. The results of research that marketing mix, the quality ofservices, and the religiousness value significantly influences to the trust ofcustomers. So, hypothesis is received. Services of marketing mix significantlyinfluences to the commitment of customers. Then, hypothesis is received. Thequality of services and the value of religiousness influence positively but notsignificantly to the commitment of customers and hypotheses is rejected. Inshort, the trust is significantly influenced by the religiousness value to thecommitment of customers. Although, the trust cannot be significantlyinfluenced the marketing mix to the commitment of customers. But, the qualityof services is significantly influenced to the commitment of customers. Fromthe results of the research, the researcher suggests to the head of the Sharia bankpublic to determine the best composition of marketing mix and it should betaken from UMKM agent because the population of Indonesia is moslem. Inaddition, the researcher hopes the next researcher can increase the indicator ormake the new indicator for the comprehensive and applicative in the Shariabank research.Key word: Marketing mix, service quality, religiousness value, trust andcommitment.Pengaruh Bauran Pemasaran Jasa, Kualitas Layanan Dan Nilai Religiusitas Terhadap Kepercayaan Nasabah danImplikasinya Pada Komitmen Nasabah Bank Umum Syariah Di Wilayah Gerbang Kertasusila Jawa Timur.